NEW AGE ATHEISM MOVEMENT: A VANISHING MEDIATOR INTO A FUTURISTIC SECULAR SOCIETY - Pacaol, Ninoval Flores (Sanata Dharma University, 2020)
The progress of natural science together with some of the crimes and violent actions committed by religions were central to the New Age Movement of Atheism since the first decade of the century. Their atheistic evangelicalism is for the secularization of society and the dissolution of religions in every aspect of human life. This paper hinges on Kahambing’s development of the concept ‘vanishing mediator’ and applies its synthesized framework as methodology. The application of the concept: a.) retroactively traces an intervention, b.) evaluates the intervention, c.) identifies the mediator, and d.) locates the vanishing point. Applying this to new age atheism, the discussion of the study is divided into three parts. First, it introduces the historical origin and atheistic interventions on religions; second, the movement is treated as a vanishing mediator or transition from religious to secular society; and lastly, it gives a futuristic account of a secular world that is rooted on the influence of new atheism in the era.